Experimental study of the influence of the damping coefficient of a semi-active suspension on vehicle acceleration during starting - Shuklinov, S.; Tkachov, О.; Шуклінов, С. М.; Ткачов, О. Ю. (Харківський національний автомобільно-дорожній університет, 2024)
Problem. The influence of the damping coefficient of a semi-active suspension on vehicle acceleration during starting can be determined experimentally. The experimental research method is the most accurate for obtaining real data, as it accounts for vehicle parameters and the specific operation of the suspension system. This study conducted an experimental investigation of the acceleration process of a vehicle equipped with a semi-active suspension. The effect of the suspension damping coefficient on vehicle acceleration was determined for the first and second gears. The vehicle selected for the study was a Land Rover Evoque equipped with a CVSA suspension system from Tenneco. Speed, acceleration, and distance parameters of the vehicle were measured under conditions of low and high suspension damping. For a clear representation of the research results, graphical dependencies of speed, acceleration, and distance on time were constructed using MATLAB software. The results were analyzed, and corresponding conclusions were drawn. Goal. The purpose of the study is to validate the theoretical research on the influence of the damping coefficient of a semi-active suspension on vehicle acceleration during starting under road conditions. Methodology. The approaches adopted in this study to achieve the objective are based on the principles of vehicle theory. Results. It has been established that a vehicle with a high suspension damping coefficient has a greater impact on acceleration in first and second gears compared to a vehicle with a low damping coefficient. It was determined that the acceleration of a vehicle with high suspension damping during first-gear acceleration is higher than that of a vehicle with low damping. During the shift from first to second gear, the suspension settings do not affect vehicle acceleration. In second-gear acceleration, the vehicle with high suspension damping also exhibits higher acceleration than with low damping. Corresponding data were obtained showing different acceleration distances for vehicles with high and low suspension damping over the same period of time. Originality. The results of the study provided an insight into the impact of suspension on vehicle acceleration when using different gears. Practical value. The results of the experimental study enable a comparative analysis of the theoretical research on the influence of the damping coefficient on vehicle acceleration. Moreover, the obtained data can be utilized in the design of new vehicles or in the improvement of sports cars, such as dragsters.
Експериментальне дослідження впливу коефіцієнту демпфування напівактивної підвіски на прискорення автомобіля при розгоні
Keywords: damping coefficient; acceleration; vehicle; starting; semi-active suspension; коефіцієнт демпфування; прискорення; автомобіль; розгін; напівактивна підвіска; 629.01; 10.30977/AT.2219-8342.2024.55.0.02